Laparoscopic percutaneous extraperitoneal closure for irreducible Amyand's hernia in a pediatric patient: A case report - Atsushi Higashio; Masahito Sato; Kosuke Endo; Kenichi Saga; Yoshiki Morotomi (Elsevier, 2023)
Introduction: Inguinal hernia is the most common pediatric surgical condition, and emergency surgery is required when the hernia is incarcerated. Occasionally, the inguinal hernia contains the appendix, which is referred to as Amyand hernia (AH). We describe a laparoscopic percutaneous extraperitoneal closure (LPEC) id an incarcerated AH. Case presentation: A 1-year-old boy presented with a bulge in the right inguinal region consistent with an inguinal hernia. Manual reduction was not possible, so we decided to proceed with a laparoscopic emergent repair. Intra-abdominal observation revealed that the cecum, the end of the ileum, and the appendix were incarcerated through the right deep internal inguinal ring, leading to the diagnosis of an AH. The hernia contents were reduced by external manual compression during surgery, and the patent processus vaginalis was closed with non-absorbable suture using the LPEC technique. The appendix was not inflammed. At 4 years of postoperative follow-up, neither recurrence of the hernia nor acute appendicitis have been observed. Conclusion: LPEC is a feasible treatment option for incarcerated AH. It allows a proper high ligation of the hernia sac, and allows evaluating the condition of the incarcerated bowel after its reduction.